THE EFFECTIVENESS OF POLICY, PLANNING, RISK ASSESMENT, DATA MANAGEMENT AND COMMUNICATION ON DISASTER PREPAREDNESS AMONG 8TH INFANTRY BRIGADE IN KELANTAN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Natural disasters are a common phenomenon in every country in the world. However, the differences between theimpact on the devastation and victims depend on how the disaster is managed and how well preparedness is arranged by theagency responsible for dealing with disaster in helping the affected victims, either natural or unnatural disaster. Good disastermanagement will consider the authorities' functions until they had a good perception from the community or society. Thisstudy examines the relationship between policy, planning, risk analysis, and data management on disaster preparedness ofInfantry Battalion personnel in the State of Kelantan in the 8th Infantry Brigade. The quantitative research method bydistributing questionnaires was used to obtain feedback on 297 respondents who were sampled for this study. This study uses aquestionnaire that contains several questions on policy, planning, risk management, data management, communication, anddisaster preparedness. The data were analysed using Statistical Package for Social Science (SPSS) version 25 and Partial LeastSquares (PLS) version 3.2.8. The dependent variables are the disaster preparedness of Infantry Battalion personnel in the 8thInfantry Brigade, while the independent variables are the policy, planning, risk analysis, and data management. The study'sfindings showed a significant relationship between all the independent variables on the disaster preparedness of the EighthBrigade personnel. In such cases, it is recommended that the Malaysian Army should scrutinize and focus on exposure to alllevels in the battalion regarding disaster management. Proposed approaches and improvements and confidence in performingand handling tasks are highly dependent on the experience and knowledge of personnel either formally or informally.Personnel who received more analysed exposure were more confident and contributed to the effectiveness of actions during themobilization of disaster operations.